Biodegradable high water vapor barrier film and preparation method thereof

By forming micro-nano-sized sheet crystals on the inside and on the surface of the biodegradable polymer film, the high melting point and hydrophobicity of saturated fatty acids or their monoglycerides is used to solve the problem of limited water vapor barrier modification effect in the prior art, and the effect of significantly improving the water vapor barrier properties of the film is achieved with a simple process and low cost.

CN119592022AActive Publication Date: 2025-03-11ZHEJIANG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411534448.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing water vapor barrier modification technology of biodegradable polymers has problems such as complex process, high cost and limited modification effect, and it is difficult to significantly improve the water vapor barrier properties.

Method used

By forming micro-nano-sized sheet crystals on the inside and on the surface of the film, the high melting point and suitable hydrophobicity of saturated fatty acids or their monoglycerides can be achieved with high hydrophobicity on the surface and high water barrier inside, thereby significantly improving the water vapor barrier properties of the film.

Benefits of technology

The water vapor barrier properties of the film have been significantly improved, and the water vapor barrier properties can reach more than 2 times that of the biodegradable matrix resin film, or even more than 10 times. The process is simple and the cost is low, and it meets the requirements of industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592022A_ABST
    Figure CN119592022A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable high water vapor barrier film and a preparation method thereof. The film comprises the following components in percentage by mass: 100wt% of biodegradable matrix resin and 1-20wt% of saturated fatty acid or monoglyceride thereof, the melting point of the saturated fatty acid or monoglyceride thereof is 50 DEG C or above, and the hydrophobic parameter calculation reference value is 5-15; the interior and the surface of the high water vapor barrier film comprise micro-nano flaky crystals formed by saturated fatty acid or monoglyceride of the saturated fatty acid. High-melting-point saturated fatty acid or monoglyceride of the saturated fatty acid directly acts on the degradable matrix resin and can be quickly crystallized on the surface and inside a resin film to form flaky crystals with micro-nano sizes, and the unique structure and morphology are combined with the hydrophobicity of the saturated fatty acid or monoglyceride of the saturated fatty acid matched with the matrix resin; meanwhile, adsorption and dissolution of water vapor on the surface and diffusion of the water vapor in the interior are reduced, and the water vapor barrier property of the film can be remarkably improved under the combined action of the two.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a biodegradable high water vapor barrier film and a preparation method thereof. Background Art

[0002] In the field of plastic products that are difficult to recycle, such as agricultural mulch films, garbage bags, compost bags, and food packaging films, the use of biodegradable films instead of traditional non-degradable films can effectively solve the environmental pollution problems caused by the widespread use of the latter. On the other hand, film products such as agricultural mulch films and food packaging films have high requirements for water vapor barrier properties, especially agricultural mulch films, which are required to effectively block the penetration of water vapor to meet the requirements of water and moisture retention. The water vapor barrier properties of the bulk biodegradable polymers that have been commercialized and applied in mulch films, such as poly (adipate-co-butylene terephthalate) (PBAT), poly (succinate-co-butylene terephthalate) (PBST), and polylactic acid (PLA), are poor, only a few tens of polyethylene. When used in agricultural mulch films, their water and moisture retention properties are far inferior to traditional polyethylene mulch films.

[0003] For these bulk biodegradable resins (taking PBAT as an example) and their film products, researchers have proposed a variety of methods to improve water vapor barrier properties, including multi-layer composites, nano-composites, surface coatings, blending modifications, etc., and multiple methods can also be used in combination.

[0004] Multilayer co-extrusion with biodegradable polymers with better water vapor barrier properties to produce multilayer films can improve their water vapor barrier properties, but there is still a lack of practical barrier layer materials with significantly higher water vapor barrier properties than PBAT and excellent processing stability and toughness. When polypropylene carbonate (PPC) and PBAT are used for multilayer composite, the water vapor barrier properties of PPC and PHA are only 2-5 times that of PBAT, and the advantages are not very significant, so the modification effect is relatively limited. Nanocomposite is the most common method for gas barrier modification, but the common melt intercalation method is difficult to achieve full stripping of layered nanofillers, and the modification effect is often limited, generally only 1-5 times. Nanocomposite in a hydrophilic state can increase oxygen barrier properties by 2 orders of magnitude, but the improvement in water vapor barrier properties is still very limited. The oxygen barrier modification effect of layer-by-layer self-assembly is better, but the water vapor barrier modification effect is still not ideal.

[0005] Melt blending is the simplest and lowest cost polymer modification method and can also be used for water vapor barrier modification of biodegradable polymers. For example, (1) Chinese invention patent CN104830035A discloses a "biodegradable composition with barrier properties" comprising 90-99.9wt% biodegradable polyester and 0.1-10wt% water repellent, with a water vapor transmission rate of ≤800g.m -2 .d-1 The waterproofing agent is a high-boiling hydrocarbon with a boiling point of ≥160°C and an HLB value of ≤10, vaseline, fatty acid esters, aromatic acid esters, silicone oil, high-carbon alcohols and their esters, and polyisobutylene, preferably a waterproofing agent with a boiling point of ≥200°C and an HLB value of 0.5-8. Most of the waterproofing agents used are not biodegradable. When 4wt% of biodegradable trioleyl glycerol and 8wt% of vaseline are blended with PBAT, the water vapor permeability of the resulting blended film is 1140g.m -2 .d -1 Its water vapor barrier property is 1.3 times that of PBAT substrate.

[0006] (2) Chinese invention patent CN104861210A discloses “a hydrophobically stable starch-based fully biodegradable resin”, which is prepared by melt blending 20-50 parts of modified starch modified with stearic acid, titanate coupling agent, aluminate coupling agent, low melting point paraffin, mineral oil, and alkenyl succinic acid with 50-80 parts of fully biodegradable polyester. Compared with the film made of unmodified starch and fully biodegradable polyester, the weight loss rate after immersion in water is reduced and the water resistance is enhanced. Some examples show that the water vapor transmission rate is increased from 3230 g·m -2 ·d -1 Down to 1120 g·m -2 ·d -1 .

[0007] (3) CN114573965A discloses "a high barrier biodegradable material and its preparation method", which is prepared by melt blending poly(furandicarboxylic acid-co-butylene glycol ester) (PBDF) and polyglycolic acid (PGA) in the presence of compatibilizers, plasticizers, anti-blocking agents, antioxidants and other additives. Compared with the PBDF / PGA blend prepared without compatibilizer, it has better compatibility, higher mechanical properties, and improved oxygen and water vapor barrier properties (up to 1 times). It can be seen that the improvement in water vapor barrier properties of these biodegradable modified materials prepared by melt blending is relatively limited and has not reached an order of magnitude improvement.

[0008] Combining melt blending with nanocomposites can further improve water vapor barrier properties. (1) CN107418163A discloses "a water vapor barrier PBAT fully biodegradable film and its preparation method", which is made by blending PBAT, a degradable water barrier agent (a mixture of animal fats or waxes and plant fats or waxes), organic modified montmorillonite, organic additives, and inorganic additives, and extruding and blowing the film. Under the combined action of the water barrier agent, additives, and nanocomposites, its water vapor permeability is increased from 1600g / (m 2 d) decreased to 280-680g.m -2 ·d -1), decreased by 57.5-82.5%, equivalent to an improvement in water vapor barrier of 2.4-5.7 times that of PBAT. (2) CN114656766A discloses a high barrier green packaging material and a preparation method thereof, which is prepared by melt blending of reactive bentonite (RBC) modified by silane coupling and biodegradable polyesters A and B, wherein the water vapor permeability coefficient of the composite material prepared by 25-30wt% PBAT, 70-75wt% PLA or PGA and 4-6wt% RBC is 61.3-83.2g·mm·m -2 ·d -1 ·atm -1 , the water vapor barrier is about 5-7 times that of PBAT.

[0009] Chinese invention patent CN104387605A discloses "a biodegradable plastic agricultural film with a surface covering film", which is characterized by comprising a biodegradable plastic base film and an oil film layer covering its outer surface, the total thickness of the agricultural film is 2-15um, the thickness of the oil film layer is 0.01-2.5um, the material forming the oil film layer is selected from high boiling point hydrocarbons, vaseline, fatty acid esters, aromatic acid esters, silicone oil, stearate or its methyl ester and glyceride, and the method of forming the oil film layer includes surface coating method and blending-blowing-diffusion method, the latter relies on the slow diffusion (1 month) of the oil film layer material to the surface and precipitation into a film. Compared with agricultural films without oil film layers, agricultural films with oil film layers have a moisture retention rate increased from 40.1% to 69.1-73.5%, but the water vapor permeation results are not disclosed.

[0010] It can be seen that the existing water vapor barrier modification technology of biodegradable polymers still has bottlenecks such as complicated process, high cost and limited modification effect. The development of biodegradable high-barrier films that can significantly improve the water vapor barrier properties (such as improving by one order of magnitude or more) and preparation technologies with simple processes, low costs and excellent modification effects are still technical problems that need to be solved urgently. Summary of the invention

[0011] The present invention aims to solve the problems of cumbersome water vapor barrier modification technology and complicated process of biodegradable compounds, and provides a high water vapor barrier film of biodegradable compounds. Saturated fatty acids or their monoglycerides form micro-nano-sized flaky crystals inside and on the surface of the film to achieve high surface hydrophobicity and high internal water resistance, thereby greatly improving the water vapor barrier of the film.

[0012] To achieve the above object, the technical solution adopted by the present invention is:

[0013] A biodegradable high water vapor barrier film, comprising, by weight, 100 wt% of a biodegradable base resin and 1-20 wt% of a saturated fatty acid or a glycerol monoester thereof; the saturated fatty acid or the glycerol monoester thereof has a melting point of above 50° C., and a hydrophobic parameter calculation reference value (XlogP, referred to as hydrophobic parameter) of 5-15;

[0014] The high water vapor barrier film has micro-nano sized flaky crystals formed inside and on the surface by saturated fatty acids or their monoglycerides. The flaky crystals have a thickness of 100-600 nm, a lateral size of 1-10 um, and an average diameter-to-thickness ratio of 5-15.

[0015] The inventors unexpectedly discovered that by directly acting on a degradable base resin with a saturated fatty acid or its monoglyceride having a relatively high melting point, it can quickly crystallize on the surface and inside of the resin film to form micro-nano-sized flaky crystals. This unique structure and morphology, combined with the hydrophobicity of the saturated fatty acid or its monoglyceride itself that matches the base resin, can simultaneously reduce the adsorption, dissolution and internal diffusion of water vapor on the surface. The combined effect of the two can significantly improve the water vapor barrier properties of the film.

[0016] In the present invention, saturated fatty acids or their monoglycerides are distributed in the form of micro-nano scale flaky crystals both inside and on the surface of the film. Inside the film, water vapor has difficulty penetrating the flaky crystals and has to bypass the flaky crystals to diffuse in the matrix resin, making the diffusion path more tortuous and longer, thereby reducing the diffusion coefficient in disguise. This can be called the "internal water barrier effect," which is similar to the effect of layered nanocomposites.

[0017] In the present invention, saturated fatty acids or their monoglycerides quickly diffuse to the film surface due to their strong hydrophobicity to generate micro-nano scale flaky crystals, which accumulate to form a rough hydrophobic layer, changing the surface from weakly hydrophilic to strongly hydrophobic, thereby inhibiting the adsorption and dissolution of water vapor, reducing the solubility of water vapor, and thus reducing the water vapor permeability coefficient and improving the water vapor barrier property. This effect can be called the "surface hydrophobic effect".

[0018] Preferably, the melting point of the saturated fatty acid or its monoglyceride is above 65°C, more preferably above 75°C;

[0019] A sufficiently high melting point can prevent the saturated fatty acids or their monoglycerides in the film from melting at the use temperature, maintaining their crystal structure, thereby achieving and maintaining high water vapor barrier properties. ℃If saturated fatty acids or their monoglycerides or other hydrophobic substances are present, it is difficult to form micro-nano scale flaky crystals inside and on the surface of the film. Even if micro-nano scale flaky crystals are formed, they will melt and be destroyed at the use temperature (such as the temperature of agricultural mulch in summer can reach above 50°C), and will not significantly improve the water vapor barrier properties.

[0020] In the present invention, the hydrophobicity of the saturated fatty acid or its monoglyceride should be significantly higher than that of the base resin but not excessively higher than that of the base resin, and the appropriate hydrophobicity parameter is 5 to 15. If the hydrophobicity parameter is too high and the hydrophobicity is too strong, such as glyceryl tristearate, it will cause obvious phase separation between it and the base resin, and defects such as cracks will appear between the dispersed phase and the continuous phase. Gases can easily pass directly through the defects, resulting in a decrease in barrier properties, and the water vapor barrier modification effect is poor.

[0021] Preferably, the hydrophobic parameter of the saturated fatty acid or its monoglyceride is 7-13.

[0022] The surface flaky crystals of the high water vapor barrier film are accumulated to form a rough hydrophobic layer, which changes the surface from weakly hydrophilic to hydrophobic, and the water contact angle is above 110°. The larger the water contact angle, the stronger the hydrophobicity and the better the water vapor barrier of the film. Preferably, the micro-nano scale flaky crystals are arranged vertically and staggeredly on the surface of the film to form a strong hydrophobic layer with a higher degree of roughness, and the water contact angle of the film surface is ≥135°. It is further preferred that the water contact angle is above 150°.

[0023] The saturated fatty acid or its monoglyceride is selected from saturated fatty acids or its monoglyceride containing 14 to 32 carbon atoms. Long-chain saturated fatty acids or its monoglyceride have more suitable hydrophobicity, melting point and the property of easily forming plate-like crystals inside and on the surface of the matrix resin, and are also biodegradable. The high water vapor barrier film made from them is fully biodegradable.

[0024] The inventors unexpectedly discovered that several saturated fatty acids or their monoglycerides can satisfy both a melting point above 50°C and appropriate hydrophobicity, forming stable micro-nano-sized flake crystals inside and on the surface of the film. Preferably, the saturated fatty acids or their monoglycerides include one or more of myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid or their monoglycerides.

[0025] Further preferably, the saturated fatty acid or its monoglyceride includes one or more of stearic acid, arachidic acid, behenic acid, glyceryl monostearate, glyceryl monoarachidate, and glyceryl monobehenate.

[0026] The biodegradable matrix resin includes polylactic acid (PLA), poly(butylene succinate) (PBS), poly(ethylene succinate) (PES), poly(butylene adipate-co-succinate) (PBSA), poly(butylene adipate-co-terephthalate) (PBAT), poly(butylene succinate-co-terephthalate) (PBST), poly(butylene adipate-co-furan dicarboxylate) (PBAF), poly(succinate ... A blended resin of one or more of poly(butylene carbonate-co-terephthalate) (PBSF), poly(butylene carbonate-co-terephthalate) (PBCT), poly(butylene carbonate-co-furan dicarboxylate) (PBCF), poly(butylene glycol terephthalate) (PBGT), poly(butylene glycol furan dicarboxylate) (PBGF), poly(butylene oxalate-co-terephthalate), and poly(butylene oxalate-co-furan dicarboxylate).

[0027] Preferably, the mass proportion of saturated fat or its monoglyceride in the high water vapor barrier film is 2-15wt%, more preferably 4-12wt%.

[0028] Preferably, the biodegradable matrix resin comprises a blend of one or more of PBAT, PLA, and PBS. Further preferably, the biodegradable matrix resin is a blend of PBAT and PLA, wherein the mass proportion of PLA is 15-25wt%.

[0029] The high water vapor barrier film also includes at least one of antioxidants, heat stabilizers, and light stabilizers, and the amount of the additives is 0.05-5wt% of the biodegradable matrix resin. The film of the present invention can also be added with additives with antioxidant, anti-thermal decomposition, light stabilization and other effects to improve other comprehensive properties of the film.

[0030] The water vapor barrier property of the high water vapor barrier film is more than twice that of the biodegradable base resin film. Only a single saturated fatty acid or its monoglyceride is used as a water barrier agent, and the amount used is not large, but the effect of improving the water vapor barrier property is very amazing. Preferably, the water vapor barrier property of the high water vapor barrier film is more than 3 times, more than 4 times, more than 8 times, or even more than 10 times, more than 20 times, or more than 40 times that of the biodegradable base resin film.

[0031] The present invention also provides a method for preparing the biodegradable high water vapor barrier film, which is characterized by comprising the steps of: mixing the biodegradable base resin and the saturated fatty acid or its monoglyceride at room temperature and then melt-blending them, and thermally processing the obtained blend to form a film to obtain the high water vapor barrier film.

[0032] In the present invention, the melt blending method includes open mixing, internal mixing and melt extrusion, preferably melt extrusion granulation, more preferably twin-screw extrusion granulation; the thermal processing film-making method includes extrusion blow molding, extrusion cast film or hot pressing film, preferably extrusion blow molding.

[0033] In the present invention, antioxidants, heat stabilizers and light stabilizers may be added during the melt blending process to improve processing stability and weather resistance. The total amount of antioxidants, heat stabilizers and light stabilizers is 0.05-5 wt % of the biodegradable base resin.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The present invention uses a saturated fatty acid or its monoglyceride with a high melting point and suitable hydrophobicity as a water barrier agent to form micro-nano-sized plate-like crystals inside and on the surface of the biodegradable substrate film, unexpectedly achieving an order of magnitude improvement in the water vapor barrier property of the film with a single component, and the improvement effect is very significant.

[0036] (2) The saturated fatty acid or its monoglyceride used in the present invention does not need to be modified or pre-treated, the formula is simple, all components of the film are fully biodegradable, and the physical, mechanical properties and biological environmental protection of the base resin can be well maintained.

[0037] (3) The modified raw materials used in the present invention, saturated fatty acids or their monoglycerides, are cheap and readily available. The film preparation method is simple, efficient, environmentally friendly, and low-cost. Existing plastic processing equipment can be used, and industrialization is easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 These are SEM images of the cross sections of PBAT membranes and various modified PBAT membranes.

[0039] Figure 2 Surface SEM images of PBAT membrane and various modified PBAT membranes. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0041] The raw materials used in the following specific embodiments are shown in Table 1. Poly(butylene adipate-co-terephthalate), referred to as PBAT, is a product of BASF, with the brand name Ecoflex F Blend C1200; polylactic acid, referred to as PLA, is a product of Natureworks, with the brand name 3251D.

[0042] Table 1 Raw materials and their basic properties used in the examples and comparative examples

[0043]

[0044] The hydrophobicity of the base resin and the hydrophobic modifier is expressed by the hydrophobic parameter calculation reference value (XlogP). The larger the XlogP value, the stronger the hydrophobicity. The XlogP value is calculated according to the reference (Wang Renxiao, Fu Ying, Lai Luhua. A new method for calculating the lipid-water partition coefficient of organic compounds [J]. Acta Physico-Chimica Sinica, 1997, 13 (1), 1-4).

[0045] In the following specific implementations, the water vapor transmission rate and water vapor permeability coefficient are measured using the moisture permeability cup method, and the test conditions are 38°C and 90% RH. The water vapor permeability coefficient (WVP, unit is g.mm.m -2 .d -1 .atm -1 ) is used to indicate the water vapor barrier property of a material. The lower the water vapor permeability coefficient, the better the water vapor barrier property. The water vapor permeability coefficient is a property of the material, while the water vapor transmission rate (WVTR, unit: g·m -2 ·day -1 ) is not a material property, but is related to the thickness of the product and the test pressure difference or relative humidity. Since the thickness of film products is often different, the water vapor permeability cannot be directly used to indicate the water vapor barrier of the material. However, the water vapor permeability coefficient can be converted into the water vapor permeability under standard thickness (10 microns, agricultural film is generally 10 microns thick) and standard test conditions (38°C, 90% relative humidity), recorded as WVTR 10 Due to the specified thickness and pressure difference (depending on the relative humidity), WVTR 10 It can also be used to indicate the water vapor barrier properties of a material.

[0046] Further, in the following specific implementations, WVP (unit: g.mm.m -2 .d -1 .atm -1) is used to represent the water vapor barrier property of the material, WVP0 is used to represent the water vapor permeability coefficient of the matrix resin film under the same processing conditions, and the water vapor barrier modification factor BIF is defined as WVP0 / WVP. BIF represents the multiple of the water vapor barrier property of the modified film compared to the matrix resin film. The larger the BIF, the better the water vapor barrier modification effect. Comparative Example 1: Pure PBAT matrix resin film

[0047] Step 1, 60 g of PBAT was placed in a vacuum drying oven at 40° C. and dried for 24 h, then added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50 rpm and 150° C. for 5 min;

[0048] Step 2: The sample obtained in step 1 is melted at 150° C. without pressure for 5 min, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 min, and then cooled on a steel plate with cold water to form a film, which is recorded as PBAT.

[0049] Comparative Example 2: PBAT + 8% lauric acid

[0050] Step 1, 60g PBAT and 4.8g lauric acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0051] Step 2: The sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-LA8.

[0052] Comparative Example 3: PBAT + 8% methyl stearate

[0053] Step 1, 60g PBAT and 4.8g methyl stearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0054] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-MS8.

[0055] Comparative Example 4: PBAT + 8% n-butyl stearate

[0056] Step 1, 60g PBAT and 4.8g n-butyl stearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0057] Step 2: The sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-BS8.

[0058] Comparative Example 5: PBAT + 8% triolein

[0059] Step 1, 60g PBAT and 4.8g glycerol trioleate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0060] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-GTO8.

[0061] Comparative Example 6: PBAT + 8% calcium stearate

[0062] Step 1, 60g PBAT and 4.8g calcium stearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 170°C for 5min to obtain a blend sample;

[0063] Step 2: The sample was melted at 170°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-CS8.

[0064] Comparative Example 7: PBAT + 8% N, N'-ethylene bis stearamide

[0065] Step 1, 60g PBAT and 4.8g N,N'-ethylene bisstearamide were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 170°C for 5min to obtain a blend sample;

[0066] Step 2, the sample was melted at 170°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-EBS8.

[0067] Comparative Example 8: PBAT + 8% Ethylene Glycol Distearate

[0068] Step 1, 60g PBAT and 4.8g ethylene glycol distearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0069] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-EDS8.

[0070] Comparative Example 9: PBAT + 8% glyceryl tristearate

[0071] Step 1, 60g PBAT and 4.8g glyceryl tristearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0072] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-GTS8.

[0073] Comparative Example 10: PBAT + 8% Pentaerythritol Tetrastearate

[0074] Step 1, 60g PBAT and 4.8g pentaerythritol tetrastearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0075] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-PETS8.

[0076] Example 1: PBAT + 8% myristic acid

[0077] Step 1, 60g PBAT and 4.8g myristic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0078] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-MA8.

[0079] Example 2: PBAT + 8% palmitic acid

[0080] Step 1, 60g PBAT and 4.8g palmitic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0081] Step 2: The sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-PA8.

[0082] Example 3: PBAT + 8% stearic acid

[0083] Step 1, 60g PBAT and 4.8g stearic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0084] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-SA8.

[0085] Example 4: PBAT + 8% Arachidic Acid

[0086] Step 1, 60g PBAT and 4.8g arachidic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0087] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-AA8.

[0088] Example 5: PBAT + 8% Behenic Acid

[0089] Step 1, 60g PBAT and 4.8g behenic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0090] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-DA8.

[0091] Example 6-8: PBAT + 2%, 4% or 12% stearic acid

[0092] The preparation process was the same as in Example 3, except that the amounts of stearic acid were changed to 2wt%, 4wt%, and 12wt%, respectively. The obtained modified PBAT films were named PBAT-SA2, PBAT-SA4, and PBAT-SA12, respectively.

[0093] Examples 9-12: PBAT + 2%, 4%, 6% or 12% arachidic acid

[0094] The preparation process was the same as that in Example 4, except that the amount of arachidic acid was changed to 2wt%, 4wt%, 6wt% and 12wt%, respectively. The obtained modified PBAT films were named PBAT-AA2, PBAT-AA4, PBAT-AA6 and PBAT-AA12, respectively.

[0095] Example 13: PBAT + 8% glyceryl monostearate

[0096] Step 1, 60g PBAT and 4.8g glycerol monostearate were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 150°C for 5min to obtain a blend sample;

[0097] Step 2, the sample was melted at 150°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT-GMS8.

[0098] Example 14: PBAT / PLA+8% Behenic Acid

[0099] Step 1, 48g PBAT, 12g polylactic acid and 4.8g behenic acid were placed in a vacuum drying oven at 40°C and dried for 24h, and then mixed evenly at room temperature; the mixture was added to a preheated HAAKE Polylab OS torque rheometer, and melt-blended at 50rpm and 165°C for 5min to obtain a blend sample;

[0100] Step 2, the sample was melted at 170°C without pressure for 5 minutes, then placed between the plates of a hot press and melted at a pressure of 10 MPa for 5 minutes, and then cooled on a steel plate with cold water to form a film, named PBAT / PLA-DA8.

[0101] Example 15: PBAT / PLA+8% Behenic Acid

[0102] Step 1, 1.6 kg PBAT, 0.4 kg polylactic acid, and 0.16 kg behenic acid are placed in a vacuum drying oven at 40° C. and dried for 24 hours, and then mixed with 4 g antioxidant 1010, 4 g antioxidant 626, and 10 g light stabilizer 1164 at room temperature; the mixture is added to a twin-screw extruder, melt-blended at 50 rpm and 185° C., and extruded into granules to obtain blend granules;

[0103] Step 2, the pellets enter the single screw extruder for melt extrusion, and the temperatures in the feeding zone, plasticizing zone, and homogenizing zone are 165°C, 175°C, and 185°C, respectively; the blend melt enters the film blowing unit, and the temperatures in the die head connection zone and the die zone are 185°C and 180°C, respectively, and is blown into a film bubble through the die, and after cooling, stretching, and winding, a film product is obtained, which is named PBAT / PLA-DA8*.

[0104] The formula, melting point, contact angle and water vapor barrier properties of the pure PBAT matrix resin film and the modified PBAT film prepared in the above comparative examples and embodiments are summarized in Table 2.

[0105] Table 2. Formulation, contact angle and water vapor barrier properties of pure PBAT matrix resin film and modified PBAT film

[0106]

[0107]

[0108] Note: X = A, B or C, representing the requirement level of water vapor transmission rate in GB / T 35795-2017: A: <800g.m -2 .d -1 ; B:800-1600g.m -2 .d -1 ; C: ≥1600g.m -2 .d -1 .

[0109] Analysis and explanation of the results in Table 2:

[0110] In Comparative Example 1, the water vapor permeability coefficient P of the PBAT matrix resin film is WV,0 419±43g·mm·m -2 ·d -1 ·atm -1 , converted to WVTR 10 2500g.m -2 .d -1 , which is equivalent to a water vapor transmission rate of 2500g.m for a PBAT film with a thickness of 10um at 38℃ / 90RH%. -2 .d -1 , only meets the Class C requirements of the national standard GB / T 35795-2017 "Fully biodegradable agricultural ground covering film" (hereinafter referred to as the national standard).

[0111] In Examples 1-5, PBAT was modified with 8 wt% of five saturated fatty acids (myristic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid) with melting points all greater than 50°C to obtain five modified films. The fatty acids formed micro-nano scale flake crystals inside and on the surface of the film, with an average thickness of 200-500 nm, a lateral size of 2-8 μm, and an average aspect ratio of 5-12 (see Figure 1 ), and the plate-like crystals on the film surface are basically arranged vertically and staggered, with a very rough hydrophobic layer (see Figure 2 ), the surface water contact angle is as high as 138-153°, and the BIF value of the modified PBAT film is 3.4-10.7, that is, their water vapor barrier property is 3.4-10.7 times that of the PBAT matrix resin film, and the water vapor barrier modification effect is significant. Except for implementation 2, all of them meet the national standard Class A requirements. Among them, the water vapor barrier property of the modified PBAT film using 8wt% arachidic acid and behenic acid is 10.7 and 10.2 times that of PBAT, that is, a modification effect of more than one order of magnitude is achieved.

[0112] Compared with Examples 1-5, Comparative Example 2 uses 8wt% lauric acid to modify PBAT. The melting point of lauric acid is 44°C, which is lower than 50°C. No lamellar crystals are generated inside and on the surface of the obtained PBAT-LA8 film. Although the surface of the film is relatively rough, the contact angle is only 111°, which is significantly lower than that of Examples 1-5. Its water vapor barrier property is even worse than that of the PBAT matrix resin film. Lauric acid is similar in structure to myristic acid, with only 2 CH2 differences, but its melting point is low and its hydrophobicity is also low. The internal and surface structures of the film obtained by blending with PBAT are very different from those of Examples 1-5, and the water vapor barrier property is also very different from that of Examples 1-5, indicating that the formation of lamellar crystals inside and on the surface of the film and the rough surface morphology contribute greatly to the water vapor barrier property, and also indicating that the low melting point is not conducive to the formation of the structure and morphology.

[0113] Comparative Examples 3-5 use low melting point methyl stearate (T m 37-41℃) and butyl stearate (T m 27.5℃) and liquid triolein (T m -5℃) to modify PBAT. These modifiers do not form plate-like crystals inside or on the surface of the film, but form small pores inside the film ( Figure 1 ), forming stripes, spherical particles or a smooth surface on the film surface ( Figure 2 ). The water vapor barrier properties of these films are worse than those of pure PBAT films, indicating that they do not play a role in water vapor barrier modification. This shows that if the melting point of the modifier is too low or it is liquid at room temperature, it will not be able to generate flaky crystals and rough surface morphology, and cannot play a good role in water vapor barrier modification.

[0114] Comparative Example 6-7: 8wt% calcium stearate (CS) and N,N'-ethylene bis stearamide (EBS) were used to modify PBAT. The melting points of these two modifiers are much higher than 50°C and they are also highly hydrophobic. However, the surface water contact angle is only about 100°. Compared with the pure PBAT film, its water vapor barrier property is not improved but worsened. Figure 1 and Figure 2 As shown, the surface of the PBAT-CS8 film is relatively smooth, with a small amount of flaky or spherical CS particles; the surface of the PBAT-EBS8 film has irregular EBS crystals and a certain degree of roughness, but the morphology is completely different from that of Examples 1 to 5. This result shows that although the long-chain saturated aliphatic metal salts or amide derivatives have high melting points and suitable hydrophobicity, they cannot form flaky crystals inside and on the surface of the film, and the film surface has no rough hydrophobic structure, so a good water vapor barrier modification effect cannot be achieved.

[0115] Comparative Examples 8-10: 8wt% of ethylene glycol distearate, glycerol tristearate, and pentaerythritol tetrastearate were used to modify PBAT. These three modifiers have high melting points (61°C, 71°C, 63°C) and higher hydrophobic parameters (17.3, 25.8, 36.2), but no lamellar crystals are formed inside the film, but obvious microphase separation occurs with the PBAT matrix resin, and there are obvious cracks at the interface. Although some lamellar crystals are formed on the surface of the film, the number is small and in a "lodging" state, the surface roughness is low, and the water contact angle is relatively low (117°, 113°, 114°). Although there is a certain water vapor barrier modification effect, its BIF values ​​are 1.40, 1.36, and 1.16, respectively, and the modification effect is limited. This result shows that the modifier is not the stronger the hydrophobicity, the better, but should have appropriate hydrophobicity, that is, its hydrophobicity should be significantly higher than the matrix resin but not too high.

[0116] The above results show that the hydrophobic modifier should have both a high melting point and appropriate hydrophobicity, and generate lamellar crystals inside and on the surface of the film and form a hydrophobic rough structure on the surface. The above three are necessary conditions for obtaining excellent water vapor barrier modification effects, and none of them can be missing.

[0117] In Examples 6-7, the amount of stearic acid was reduced to 2-4wt%, and its water vapor barrier reached 1.5-2.2 times that of the PBAT film. Compared with Example 3 (the amount of stearic acid was 8wt%), the modification effect was reduced, but a good water vapor barrier modification effect was still achieved, reaching the national standard C and B requirements respectively. In Example 8, the amount of stearic acid was increased to 12wt%, and its water vapor barrier reached 4.49 times that of the PBAT film. Compared with Example 3 (the amount of stearic acid was 8wt%), the modification effect was further improved and reached the national standard A requirements. This shows that the amount of modifier has an important influence on the modification effect. As the amount increases, the surface hydrophobicity increases (the contact angle increases), and the water vapor barrier improves.

[0118] In Examples 9-11, the amount of peanut acid was reduced to 2wt%, 4wt%, and 6wt%, respectively. Compared with Example 4, the modification effect was reduced, but a good water vapor barrier modification effect was still achieved. The water vapor barrier properties were 1.50 times, 2.50 times, and 4.69 times that of PBAT, respectively, meeting the national standard C, B, and A requirements. In Example 12, the amount of peanut acid was increased to 12wt%, and the contact angle of the obtained PBAT-AA12 film was as high as 152°. The surface was super hydrophobic, and its water vapor barrier property was further significantly improved compared with Example 4, up to 46.6 times that of the PBAT film, achieving an extremely excellent water vapor barrier modification effect. This further illustrates that the type and amount of the modifier have an important influence on the water vapor barrier modification effect. Compared with stearic acid, as the amount of peanut acid increases, the surface hydrophobicity is more significantly enhanced, and the water vapor barrier property is also more significantly improved.

[0119] Example 13 uses 8wt% of glycerol monostearate to modify PBAT. Stearic acid glycerol monostearate still forms flaky crystals inside and on the surface of the film. A small part of the flaky crystals on the surface are staggered perpendicular to the film surface, and most of them are in a "falling" state. Therefore, its water contact angle is only 110°, which is significantly less than 153° and 148° of Examples 4-5. The water vapor barrier modification effect is lower than that of Examples 4-5, but it still achieves a modification effect equivalent to that of Example 3, meeting the national standard Class A requirements. This further illustrates that the extremely rough surface morphology formed by the flaky crystals on the film surface staggered perpendicular to the film surface has an important influence on the water vapor barrier property.

[0120] Example 14 uses two biodegradable polyesters, PBAT and PLA, as the base resins, and uses 8wt% DA to modify the water vapor barrier. The water vapor barrier of the PBAT / PLA-DA8 film is 8.2 times that of the PBAT / PLA blend film, meeting the national standard Class A requirements. This shows that the water vapor barrier modification is also applicable to the blend film of biodegradable polymers.

[0121] The formula of Example 15 is basically the same as that of Example 10, except that 0.05wt% of antioxidant 1010 and 0.2wt% of antioxidant 626 are added, a twin-screw extruder is used for blending, and a single-screw extruder + film blowing machine is used for film blowing. The obtained PBAT / PLA-DA8 film has a water contact angle of up to 146°, and the water vapor barrier modification effect is still very good. The BIF is as high as 8.7, which is slightly better than Example 10 and meets the national standard Class A requirements.

[0122] In summary, the WVTR shown in Table 1 10 The results show that the water vapor barrier property of the modified PBAT film prepared with 2wt% of saturated fatty acids or their monoglycerides can meet the national standard C requirements; the water vapor barrier property of the modified PBAT film prepared with 4wt% of saturated fatty acids or their monoglycerides can meet the national standard B requirements; the water vapor barrier property of the modified PBAT film prepared with 8wt% of saturated fatty acids or their monoglycerides can mostly meet the national standard A requirements. The tensile properties of the PBAT films and modified PBAT films prepared in Comparative Example 1, Examples 1-12 and 14 are summarized in Table 3. It can be seen that compared with the PBAT film (Comparative Example 1), the tensile modulus (E) of the PBAT film modified with 8wt% of long-chain saturated fatty acids containing 14-22 carbon atoms is increased from 106MPa to 122-137MPa, and the tensile strength (σ b ) dropped from 20.4MPa to 15.7-16.2MPa, and the elongation at break (ε b )423% increased to 442-493%, indicating that the use of these saturated fatty acids to modify PBAT will result in a significant decrease in its tensile strength, but the tensile modulus and toughness are improved. The results of Examples 3 and 6-8 and 4 and 9-12 show that as the amount of stearic acid or arachidic acid increases, the modulus tends to increase, the strength tends to decrease, and the elongation at break does not change significantly, so the amount should not be too high.

[0123] The results of Example 14 show that the PBAT / PLA-DA8 film prepared by replacing PBAT with a blend of 80 wt% PBAT and 20 wt% PLA as the base resin has significantly higher tensile modulus (485±55 MPa) and tensile strength (24.9±0.9 MPa) than the PBAT-DA film (Example 5) and the PBAT film (Comparative Example 1), and the elongation at break is slightly decreased, which indicates that the use of a blend of multiple biodegradable polyesters as a base resin and blending with saturated fatty acids to prepare a film helps to maintain or even improve the mechanical properties of the biodegradable high water vapor barrier film.

[0124] Table 3 Tensile mechanical properties of PBAT film, PBAT-DA8 film and PBAT / PLA-DA8 film

[0125]

[0126]

Claims

1. A biodegradable high water vapor barrier film, characterized in that: The composition comprises 100 wt% of a biodegradable base resin and 1-20 wt% of a saturated fatty acid or a monoglyceride thereof; The melting point of the saturated fatty acid or its monoglyceride is above 50° C., and the reference value of the hydrophobic parameter calculation is 5-15; The high water vapor barrier film comprises micro-nano sized plate-like crystals formed by saturated fatty acids or their monoglycerides inside and on the surface.

2. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The saturated fatty acid or its monoglyceride is selected from saturated fatty acids or its monoglyceride containing 14-32 carbon atoms.

3. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The saturated fatty acid or its monoglyceride includes one or more of myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid or their monoglycerides.

4. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The biodegradable base resin includes a blended resin of one or more of polylactic acid, poly(butylene succinate), poly(ethylene succinate), poly(butylene adipate-co-succinate), poly(butylene adipate-co-terephthalate), poly(butylene succinate-co-terephthalate), poly(butylene adipate-co-furandicarboxylate), poly(butylene succinate-co-furandicarboxylate), poly(butylene carbonate-co-terephthalate), poly(butylene carbonate-co-furandicarboxylate), poly(glycolic acid-co-terephthalate), poly(glycolic acid-co-furandicarboxylate), poly(oxalic acid-co-terephthalate), and poly(oxalic acid-co-furandicarboxylate).

5. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The melting point of the saturated fatty acid or its monoglyceride is above 65° C., and the calculated reference value of the hydrophobic parameter is 7-13.

6. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The high water vapor barrier film further comprises at least one auxiliary agent selected from the group consisting of an antioxidant, a heat stabilizer and a light stabilizer, and the amount of the auxiliary agent is 0.05-5wt% of the biodegradable base resin.

7. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The surface water contact angle of the high water vapor barrier film is above 110°C.

8. The biodegradable high water vapor barrier film according to claim 1, characterized in that: The water vapor barrier property of the high water vapor barrier film is more than twice that of the biodegradable base resin film.

9. The method for preparing a biodegradable high water vapor barrier film according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing a biodegradable base resin and the saturated fatty acid or its monoglyceride at room temperature, then melt-blending the mixture, and subjecting the obtained mixture to thermal processing and film-forming to obtain the high water vapor barrier film.

10. The method for preparing a biodegradable high water vapor barrier film according to claim 9, characterized in that: The melt blending method is twin-screw extrusion, and the thermal processing film-making method is extrusion blow molding, extrusion casting or hot pressing.

Citation Information

Patent Citations

  • Biodegradable agricultural plastic film with surface cover film

    CN104387605A

  • Biodegradable composite with barrier property and preparation method and applications thereof

    CN104830035A

  • Starch-base fully biodegradable resin with steady hydrophobic property and preparation method thereof

    CN104861210A

  • High-barrier biodegradable material as well as preparation method and application thereof

    CN114573965A

  • High-barrier green packaging material and preparation method thereof

    CN114656766A